Framing Media Online atas Pemberitaan Isu Lingkungan Hidup Dalam Upaya Pencapaian Keberhasilan SDGs Indonesia - Xenia Angelica Wijayanto; Lestari Nurhajati (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
The Sustainable Development Goals (SDGs), that have been carried out by Indonesia, are global programs launched by the United Nations since September 2015. This is proven by the Presidential Regulation No. 59 / 2017 about the Implementation of Achievement of Sustainable Development Goals which was inaugurated by President Jokowi in July 2017. Among 17 SDGs points, there are 6 points that talk about environmental issue. This shows the importance of environmental issues that are now a global concern. Information about SDGs to public is still not massive, even though SDGs socialization is very important for the society so that the final goal of SDGs in Indonesia will be successful in 2030. The aim of this study is to find ways for media that can fix current environmental problems and problems experienced by Indonesian SDGs. This study used Environmental Communication concept. For the methodology, this study uses framing from Pan & Kosicki, with 4 of the most frequently accessed online media in Indonesia, in 2018 namely Detik.com, Tribunnews.com, Kompas.com, and Liputan6.com. Pre-research results show that online media contains very little news about environmental issues in their program, implementation and process of achieving Indonesia's SDGs success.